EFFECT OF FSH, PMSG ON SUPEROVULATO~Y RESPONSE AND EMBRYO RECOVERY RATE IN TELLICHERRY GOATS - PALANISAMY, A; BALASUBRAMANIAN, S; RANGASAMY, S (The Indian Journal of Animal Reproduction, 2011)
The mean onset of estrum was 26.18±0.70 and 17.85±0.44 h in the FSH and PMSG group, respectively. Inthe present study, the onset of estrum was significantly (P
Keywords: Goat; Embryo transfer; Superovulation and Embryo recovery